IMPLEMENTASI E-GOVERNMENT DI KANTOR SAMSAT PROVINSI KALIMANTAN TIMUR KOTA SAMARINDA - Gesit Pradana Suriyansyah (ADMINISTRASI PUBLIK, 2018)
Gesit Pradana Suriansyah Putra, 2018, Implementation of E-Government in Samsat Office of East Kalimantan Province of Samarinda City. Supervisor: Mrs. Dr.Hj.Futum Hubaib, S.Sos, M.Si and Mr. Dr.Marjoni Rachman, M.Si.The purpose of this research is to know the Implementation of E-Government in Samsat Office of East Kalimantan Province of Samarinda City.With the above objectives, the analytical tool used in this study is descriptive qualitative analysis. Factors used in this research are Network Preparedness, Management Efficiency, Public Participation, and Online Services. With this analysis the authors will analyze various data collected from various sources then presented in detail in the form of descriptive.Based on the analysis conducted on various sources of data collected, that Implementation of E-Government in Samsat Office of East Kalimantan Province of Samarinda City when viewed through the four factors above can be said to run well and effectively. But there are still obstacles inhibiting the effectiveness of these services as the implementation.